(untitled) (Research, Society and Development, 2021)
This paper aims to make a comparative analysis between Regular High School (EMR) and Youth and Adult Education (EJA, in Portuguese), in the context of a State public education institution in the State of Goiás. 3rd series of EJA. In this sense, we seek to understand whether the approach in teaching chemistry to EJA promotes significant learning when compared to EMR. As proposed methodology, qualitative, exploratory, documentary and bibliographic research was used. As for the procedures, we analyzed the Reference Curriculum for teaching chemistry in both modalities, as well as the development and application of questionnaires for teachers and students, as well as semi-structured interviews with teachers and pedagogical coordinators of both modalities. We infer, from this research, that EJA students, in the context in which we developed this research, have a greater conceptual gap when compared to EMR students. Thus, we believe that the adoption of pedagogical practices that take into account the particularities existing in EJA is a sine qua non condition. However, in both modalities, there is a need to resume the discussion about the purposes of teaching Chemistry, since this, as it has been addressed, has distanced students from the real understanding and objective of Chemistry in secondary school.